Influence of Nanoscale Roughness on Flotation (ABSTRACT PAGE) - Scott C. Brown; Ivan U. Vakarelski (International Mineral Processing Congress, 2003)
The particles commonly encountered in mineral benefication schemes have irregularites that are expressed at many different length scales. In part, this originates from preceding processes (e.g. makedown, comminution, handling and storage), which are known to chemically and physically modify the bulk particle and its surface. Interparticle tribology, dissolution and reprecipitation events along with large-scale mechanical stresses are just a handful of the interactions encountered during processing of particles prior to separation. It is feasible to imagine that each one of these events may impose a fingerprint of characteristic nanoscale, microscale, and macroscale morphological changes that can modify the overall interaction of these particles within a system. Suprisingly there are just a few works on how these resulting features can alter the performance of benefication schemes, and especially flotation.